Work Environment, Work Discipline, and Job Satisfaction: Strategic Pathways to Enhancing Employee Performance - Widiawati, Andi; Roswiyanti, Roswiyanti; Suci, Yuli Rahmini; Irdawati, Irdawati; Yuliany, Nur (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the influence of the work environment and work discipline on employee performance, with job satisfaction as a mediating variable at the Makassar City Transportation Agency. Its contribution lies in clarifying how justice theory and performance management perspectives jointly explain the interplay between organizational fairness, discipline, satisfaction, and performance in the public sector. Using a quantitative approach, data were collected from 195 employees through saturated sampling, with analysis conducted via PLS-SEM using SmartPLS. Results reveal that the work environment and work discipline directly and significantly enhance employee performance. However, neither variable significantly affects job satisfaction, and satisfaction does not mediate their effects, though it independently contributes positively to performance. These findings underscore that performance improvement is best achieved through strengthening fairness in the work environment and cultivating consistent discipline, while enhancing satisfaction requires complementary strategies such as career development, rewards, and effective communication.